Potential of seven insulin resistance indicators as biomarkers to predict infertility risk in U.S. women of reproductive age: a cross-sectional study - Ruihua Yan; Jiao Zhang; Hongyun Ma; Yang Wu; Yang Fan (Reproductive Biology and Endocrinology)
Abstract Background Insulin resistance(IR) is a key mechanism underlying both obesity and metabolic syndrome, with significant implications for the onset and progression of female infertility. This study systematically examines the associations between seven insulin resistance indicators and the risk of infertility in U.S. women of reproductive age, while also evaluating the diagnostic value of these indicators in predicting infertility. Method This cross-sectional study analyzed data from the 2013–2018 National Health and Nutrition Examination Survey (NHANES) to explore the relationship between seven insulin resistance indicators and infertility risk. The indicators included the Metabolic Score for Insulin Resistance (METS-IR), Triglyceride-Glucose Index (TyG), Triglyceride-Glucose-Waist Circumference (TyG-WC), Triglyceride-Glucose-Body Mass Index (TyG-BMI), Triglyceride-Glucose-Waist-to-Height Ratio (TyG-WHtR), Homeostasis Model Assessment of Insulin Resistance (HOMA-IR), and Triglyceride/High-Density Lipoprotein Ratio (TG/HDL). Receiver Operating Characteristic (ROC) curves were used to assess the diagnostic accuracy of each insulin resistance indicator in predicting infertility. Additionally, smooth curve fitting and threshold effect analysis were employed to further explore the relationship between insulin resistance indicators with high diagnostic efficacy and infertility. Results This study included 1,100 women aged 20–45, of whom 140 (12.61%) were diagnosed with infertility. The results revealed significant positive correlations between METS-IR, TyG-BMI, TyG-WC, TyG-WHtR, and infertility risk. Specifically, as TyG-WC and TyG-WHtR levels increased, the risk of infertility rose linearly, while METS-IR and TyG-BMI exhibited a nonlinear positive association with infertility risk. No significant correlations were observed between TyG, HOMA-IR, TG/HDL, and infertility. Finally, ROC curve analysis indicated that METS-IR outperformed the other six insulin resistance indicators in predicting infertility risk. Conclusion METS-IR, TyG-BMI, TyG-WC, and TyG-WHtR are significantly associated with the risk of infertility in U.S. women of reproductive age, with METS-IR demonstrating the highest predictive power. These findings suggest that METS-IR may have substantial clinical utility in evaluating infertility risk.